2004
DOI: 10.21273/horttech.14.1.0124
|View full text |Cite
|
Sign up to set email alerts
|

Producing and Marketing Strawberries for Direct Market Operations

Abstract: The costs associated with growing, harvesting and marketing strawberries (Fragaria × ananassa) using the plasticulture production system were estimated to be $13,540/acre ($33,457/ha). Net revenue analysis showed that growers would have to charge at least $0.85 and $1.40/lb ($1.87 to $3.09/kg) for pick-your-own (PYO) and prepicked fruit, respectively, and sell 12,000 lb of berries per acre (13,449.9 kg·ha-1) to cover this expens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…For the period from 2000 to 2003, average yields per ha in the plasticulture system in North Carolina fluctuated between 22 and 30 MTÁha -1 (Boriss et al, 2006), or %590 to 810 g/plant (assuming 36.9 thousand plants/ ha with double-row plant beds and spacing in the row of 35.6 cm and 1.52 m between rows). Safley et al (2004) estimated typical production and marketing costs for this system to be %$33,460 ha. By achieving a marketable yield of only 13.4 MTÁha -1 (364 g/plant), a slightly positive net return of $511 ha ($207 per acre) can be achieved with a pick-your-own price of $1.87 kg ($0.85 lb) and prepick (ready pick) price of $3.08 kg ($1.40 lb) (Safley et al, 2004).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For the period from 2000 to 2003, average yields per ha in the plasticulture system in North Carolina fluctuated between 22 and 30 MTÁha -1 (Boriss et al, 2006), or %590 to 810 g/plant (assuming 36.9 thousand plants/ ha with double-row plant beds and spacing in the row of 35.6 cm and 1.52 m between rows). Safley et al (2004) estimated typical production and marketing costs for this system to be %$33,460 ha. By achieving a marketable yield of only 13.4 MTÁha -1 (364 g/plant), a slightly positive net return of $511 ha ($207 per acre) can be achieved with a pick-your-own price of $1.87 kg ($0.85 lb) and prepick (ready pick) price of $3.08 kg ($1.40 lb) (Safley et al, 2004).…”
mentioning
confidence: 99%
“…Safley et al (2004) estimated typical production and marketing costs for this system to be %$33,460 ha. By achieving a marketable yield of only 13.4 MTÁha -1 (364 g/plant), a slightly positive net return of $511 ha ($207 per acre) can be achieved with a pick-your-own price of $1.87 kg ($0.85 lb) and prepick (ready pick) price of $3.08 kg ($1.40 lb) (Safley et al, 2004). However, a grower achieving 22.4 MTÁha -1 (607 g/plant), or %20,000 lb per acre, could realize a net revenue of $18,720 ha ($7,576 per acre) (Safley et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, the timing depended on work force availability and planting dates. Reference [18] reported that preplant operations were the most expensive operations in a system with plug-plants planted on raised beds. The cost associated with planting, care and harvest in the first production year are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Gross returns can range from $21,000 to just over $30,000 per acre with an estimated $13,556 in total harvest and production costs per acre (Sydorovych et al, 2006). Most strawberry enterprises in this region comprise small to mid-sized family farms with an average size of 3-5 acres (Safley et al, 2004). These farms can be managed more intensely and are more likely to use alternative farming systems compared with large-acreage operations.…”
mentioning
confidence: 99%